Strengthening the Role of Village-Owned Enterprises (Bumk) in Improving the Economy of Pegat Bukur Village in Berau Regency - Sofyan, Edwin; Sukristyanto, Agus; Handoko, V. Rudy (Indonesian Journal of Advanced Research, 2024)
This study discusses the role of Village-Owned Enterprises (BUMK) in improving the economy of Pegat Bukur Village in Berau Regency. BUMK is a legal entity established by the village to manage business and productivity to improve the welfare of the village community. This study uses a descriptive qualitative approach. The focus of the research is to identify and analyze the BUMK program in managing the potential of Pegat Bukur Village, analyze the role of BUMK in improving the village economy, and develop a model for the development of BUMK Batu Bual Sejahtera. The results of the study show that the Batu Bual Sejahtera BUMK in Pegat Bukur Village has a significant role in improving the village economy. BUMK Batu Bual Sejahtera is able to take advantage of the potential of the village into 17 business units. Through various business units that have been formed, BUMK Batu Bual Sejahtera is able to play a role in increasing community income, opening new jobs and reducing unemployment, helping the village financial sector with the potential for village original income, and community involvement in village development. BUMK also has an impact by increasing people's income, reducing the unemployment rate and independence of Kampung Pegat Bukur. The development of BUMK Batu Bual Sejahtera uses a development model with a Pentahelix actor approach where there are governments, communities, companies (Business), academics and the media.